SOCIAL ATTITUDES AND BELIEFS OF SIGHTED PEOPLE TOWARDS VISUALLY IMPAIRED - Papadaki, Maria; Tzvetkova-Arsova, Mira (Specijalna edukacija i rehabilitacija, 2013)
The purpose of this study is to find out what are the contemporary beliefs and social attitudes of Greek sighted people towards visually impaired. Blindness has been interpreted in different, often controversial ways, since ancient times. It has been also stereotyped and labeled by sighted people and has thus affected the acceptance of Visually Impaired, the tolerance towards them and their integration into societal life. Firstly, visually impaired people are still treated with some prejudice concerning the size of their disability, their education and their integration into society. However, they have ceased to apply antiquated perceptions based on fear or ignorance. Sighted people no longer believe that blind individuals are beggars, evil or blinded because of a punishment. Secondly, sighted people still believe that blind persons possess some extra powers and abilities such as better sense of things, especially of hearing, sixth sense or better judgment abilities. Finally, the common belief about associating blind people with their musical talents and skills is no longer in actual existence. Key words: visual impairment, social attitudes, sighted people